Evaluating users’ emotions for Kansei-based Malaysia higher learning institution website using Kansei checklist - Punitha Turumogan; Aslina Baharum; Ismassabah Ismail; Nor Azida Mohamed Noh; Nur Shahida Ab Fatah; Noorsidi Aizuddin Mat Noor (Bulletin of Electrical Engineering and Informatics, 2019)
Emotions play a crucial role in human-computer interaction. Emotion research in the field of human-computer interaction has only started recently and continuously evolving through the investigation and understanding of emotional effects. Thus, it forms an intelligent interaction between human and computer by responding effectively to the humans’ feelings. Emotional design generates remarkable user experiences for websites as the emotional experiences create an intense impression on our long-term memory. Recent scientific findings recommend emotional elements to be considered in designing websites as emotions influences one’s perception, conception and decision-making throughout the interaction with a website. A poorly designed user interface leads to bad user interaction while rising the users’ arousal and a displeasing user experience with a website elicits dissatisfaction emotion where consecutively results in avoidance and prevents revisit to the website. This proves the importance of emotional engagement in a website design. This research evaluated users’ emotions toward a Malaysian higher learning institution website which was designed in accordance with the standard Kansei-based web design guideline. The result justified the standard Kansei-based web design guideline for website of higher learning institutions in Malaysia.